2020
DOI: 10.1080/21688370.2020.1748459
|View full text |Cite|
|
Sign up to set email alerts
|

Optimization of an oral mucosa in vitro model based on cell line TR146

Abstract: During the last years, the popularity of saliva has been increasing for its applicability as a diagnostic fluid. Blood biomarker molecules have to cross the blood-saliva barrier (BSB) in order to appear in saliva. The BSB consists of all oral and salivary gland epithelial barriers. Within this context, the optimization of in vitro models for mechanistic studies about the transport of molecules across the oral mucosa is an important task. Here, we describe the optimization and comprehensive characterization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 79 publications
1
22
0
Order By: Relevance
“…Further work by Lin at al. showed that when culture conditions of TR146 cells were optimized by e.g., adjusting the cell culture medium, barrier properties could be improved, making the model suitable for (drug) transport and permeability studies [ 24 ]. Apart from drug permeability, TR146 cells are also used to study nanoparticle interactions and cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Further work by Lin at al. showed that when culture conditions of TR146 cells were optimized by e.g., adjusting the cell culture medium, barrier properties could be improved, making the model suitable for (drug) transport and permeability studies [ 24 ]. Apart from drug permeability, TR146 cells are also used to study nanoparticle interactions and cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Primer sequences are shown in Table 1 and were verified with PrimerBLAST [ 25 ]. Prior to usage in qPCR, amplicon sizes were evaluated using 2% agarose gels, described in detail in Lin et al [ 21 ], followed by a two-fold dilution series for calculation of primer efficiency performed via qPCR similarly as described by Pfaffl [ 26 ]. Primer efficiency was required to be 80–120% to pass for further usage.…”
Section: Methodsmentioning
confidence: 99%
“…To further investigate the relevance of CRP as a salivary biomarker, we aimed to study the transport of CRP across in vitro models of the blood–saliva barrier (BSB), defined by the epithelial cell layers of the oral mucosa and salivary glands [ 20 ]. The human buccal mucosa carcinoma cell line TR146 was chosen as an oral mucosa model, which was recently thoroughly characterized by Lin et al [ 21 ] for its biological barrier properties including expression studies of 96 relevant barrier molecules (cytokeratins, mucins, aquaporins, epithelial-mesenchymal transition (EMT) markers, and tight junction proteins among others) and validation against human buccal biopsy samples. Additionally, the integrity of the paracellular barrier was improved by optimization of the cultivation media and conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Parental HTB-41 cells were seeded in McCoy media at passages 5-12, isolated clones from cell line HTB-41 were seeded at passage 5-12 after single cell cloning at passage 8. Seeding procedure of TR146 was described in detail previously [22].…”
Section: Transwell Studiesmentioning
confidence: 99%
“…Experiments were performed on day 29 after seeding. Cultivation and seeding procedure of TR146 cells in Transwell ® models was described in detail previously [22]. On the day of transport studies TEER was measured in both models as described above in the respective cultivation media, washed twice on the apical and basolateral side with 300 µL or 900 µL basal McCoy media (McCoy's 5A media without supplements) for clone B2 or Hank´s Balanced Salt Solution (HBSS; Sigma-Aldrich; St. Louis, MO, USA; H6648) for TR146.…”
Section: Transport Studies With Ferritinmentioning
confidence: 99%